2023
DOI: 10.1002/adma.202303444
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Fluorinated Graphene Nanosheets Enables Ultrafast Lithium/Sodium/Potassium Primary Batteries

Abstract: Fluorinated carbon (CFx) is considered as a promising cathode material for lithium/sodium/potassium primary batteries with superior theoretical energy density. However, achieving high energy and power densities simultaneously remains a considerable challenge due to the strong covalency of the C‐F bond in the highly fluorinated CFx. Herein, an efficient surface engineering strategy combining surface defluorination and nitrogen doping enables fluorinated graphene nanosheets (DFG‐N) to possess controllable conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the inset in Figure b illustrates the interfacial coherence between the SEO-QSCE and the metallic lithium electrode. The initial impedance spectra of the interface display semicircular patterns in the high-frequency regions, which is an indicator of the charge-transfer impedance ( R ct ) . Remarkably, the value of R ct for the SEO-QSCE before and after polarization is measured at 51 and 50 Ω, respectively.…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the inset in Figure b illustrates the interfacial coherence between the SEO-QSCE and the metallic lithium electrode. The initial impedance spectra of the interface display semicircular patterns in the high-frequency regions, which is an indicator of the charge-transfer impedance ( R ct ) . Remarkably, the value of R ct for the SEO-QSCE before and after polarization is measured at 51 and 50 Ω, respectively.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The initial impedance spectra of the interface display semicircular patterns in the high-frequency regions, which is an indicator of the chargetransfer impedance (R ct ). 50 Remarkably, the value of R ct for the SEO-QSCE before and after polarization is measured at 51 and 50 Ω, respectively. The calculated area resistance between SEO-QSCE and the Li sheet is 39.3 Ω cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[24] In recent years, it has been found that adding defects in the electrodes can improve conductivity, cycle stability, and rate performance. [38] Chang and coworkers [39] used first-principles method to study the insertion and diffusion behavior of lithium ion in TiO 2 with and without oxygen deficiencies. The narrowing of the bandgap and the shift of the Fermi level indicate that the electronic conductivity increases after the introduction of oxygen vacancies.…”
Section: Promoting Ion Diffusion and Charge Transport Of Electrodesmentioning
confidence: 99%
“…Constructing a true GDE is relatively straightforward in aqueous electrolytes, where hydrophobic components like polytetrafluoroethylene can be used to create a solid-gas-electrolyte three-phase interface. [34][35][36] However, in non-aqueous electrolytes, the lack of solvent-phobic components makes it challenging to construct a true GDE. Consequently, the porous electrodes in non-aqueous-based metal-air batteries are often flooded with electrolytes and deprived of efficient pathways for gas mass transport, resulting in low current densities.…”
Section: Introductionmentioning
confidence: 99%